Effectiveness Of Reality Group Counseling Based On The Values Of The Quran To Improve The Responsibility Of Students Of Madrasah Aliyah In Prayer Worship - Emi Rizqil Fauziyah; M. Ramli; Adi Atmoko (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
The purpose of this study was to determine the effectiveness of reality group counseling based on the Qur'an to improve students' responsibility for prayer worship. This study used an experimental pretest-posttest one-group design. There are two types of instruments used, namely data collection instruments and experimental guides. The experimental guide consists of a reality group counseling book based on Qur'anic values, a guide for counselors, while the measuring instrument consists of a scale of responsibility for prayer worship developed from Lickona's theory. The results of the validity test using Pearson Product-Moment showed that all items had a significance of <0.05; it can be said that all items were valid with a correlation coefficient between 0.262-0.644. The results of the reliability test showed a Cronbach's Alpha value of 0.856, which means that the scale of responsibility for prayer worship used was reliable. Based on the Wilcoxon test in the group, a sig. A value of 0.005 <0.05 was obtained. then there is a statistically significant difference between the pretest and posttest measurements, rejecting the null hypothesis and accepting H1. It can be said that group counseling based on Al-Quran values is effective in increasing students' responsibility in carrying out prayer.